CONTINUITY OF MIDWIFERY CARE FOR MRS. F EXPERIENCING UMBILICAL CORD ENTANGLEMENT AT MANDREHE HEALTH CENTER, MANDREHE DISTRICT, WEST NIAS REGENCY, IN 2025 - Gulo, Wendi Idol Sryningsih; Sinaga, Siti Nurmawan; Rumondang; Ria Lolyta; Mei Elizabeth Simatupang; Rosalina Simbolon; Nika Aklima (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Comprehensive midwifery care is a strategic effort to reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in line with the Sustainable Development Goals (SDGs). Umbilical cord entanglement is a labor complication that can cause asphyxia or even fetal death if not managed correctly. Objective: To provide comprehensive continuity of care to Mrs. F from the third trimester of pregnancy, childbirth with umbilical cord entanglement, postpartum, newborn care, to family planning services. Methods: A descriptive case study using Varney’s 7-step midwifery management and SOAP documentation. The subject was Mrs. F (26 years old, G3P2A0) at Mandrehe Health Center, West Nias Regency. Results: During pregnancy, physiological complaints of frequent urination were managed through fluid intake education. During the second stage of labor, a single loop of umbilical cord entanglement was found around the baby’s neck and successfully managed by loosening the cord. The baby was born spontaneously, healthy, male, weighing 3,500 grams, length 51 cm, with an APGAR score of 10. The postpartum period was normal across four visits, the newborn received complete basic immunizations, and the mother chose the Lactational Amenorrhea Method (LAM) for contraception. Conclusion: The implementation of comprehensive care proved effective in early detection and management of umbilical cord entanglement complications, ensuring the safety of both mother and baby.